Liberia health system's journey to long-term recovery and resilience post-Ebola: a case study of an exemplary multi-year collaboration - Ako-Egbe, Louis; Seifeldin, Redda; Saikat, Sohel; Wesseh, Sanford C.; Bolongei, Moses Brown; Ngormbu, Ballah Jusu; George, Roseline; Ocan, Charles; Peter Lasuba, Clement Lugala (Frontiers in Public Health, 2023)
Liberia is one of the three countries worst hit by the 2014-2016 West Africa Ebola Virus disease (EVD) outbreak, which recorded over 10,000 cases, including health workers. Estimates suggest that the non-EVD morbidity and mortality resulting from the collapse of the health system exceeded the direct impact of EVD. Lessons from the outbreak were clear, not only for Liberia but also for the regional and global communities: that building health system resilience through an integrated approach is an investment in population health and wellbeing, as well as economic security and national development. It is therefore no surprise that Liberia made recovery and resilience a national priority from the time the outbreak waned from 2015. The recovery agenda provided the platform for stakeholders to work towards restoration of the pre-outbreak baseline of health system functions while aiming to build a higher level of resilience, informed by lessons from the Ebola crises. Based on the co-authors’ experiences of on-the-ground country-support work, this paper sort to provide an overview of the Liberia Health Service Resilience project (2018-2023) funded by KOICA, and propose a set of recommendations for national authorities and donors, derived from the authors’ perceptions of best practices and key challenges associated with the project. We used both quantitative and qualitative approaches to generate the data represented in this paper by reviewing published and unpublished technical and operational documents, and datasets derived through situational and needs assessments and routine monitoring and evaluation activities. This project has contributed to the implementation of the Liberia Investment Plan for Building a Resilient Health System and the successful response to COVID-19 outbreak in Liberia. Although limited in scope, the Health Service Resilience project has demonstrated that health system resilience could be operationalized by applying a Catchment and Integrated approach and enforcing multi-sectoral collaboration, partnership, local ownership and promoting the Primary Health Care approach. Principles applied in this pilot could guide the operationalization of health system resilience efforts in other resource-limited settings as Liberia.